Comparison of 8/6 radial and axial flux switched reluctance machines. Issue 6 (24th October 2019) - Aydoun, Racha; Parent, Guillaume; Tounzi, Mounaim; Lecointe, Jean-Philippe; Komeza, Krzysztof
Abstract : Purpose: This paper aims to deal with a performance comparison of an 8/6 radial-flux switched reluctance machine (RFSRM) and an axial-flux switched reluctance machine (AFSRM), presenting equivalent active surfaces. Design/methodology/approach: An axial machine was designed based on the equivalent active surfaces of a radial one. After estimating the machine inductances with a reluctance network, finite elements numerical models have been implemented for a more precise inductance determination and to estimate the electromagnetic torque for both machines. Finally, the AFSRM was thoroughly examined by analyzing the impact of some geometric parameters on its performance. Findings: The comparison of the RFSRM and AFSRM at equivalent active surfaces showed that the obtained axial machine is more compact along with an improvement in the electromagnetic torque. Practical implications: The equivalent AFSRM is more compact, therefore more interesting for transport and on-board applications. Originality/value: The RFSRM and AFSRM performance comparison using the same active surfaces has not been done. Moreover, the AFSRM presented has a rare design with no rotor yoke and where the rotor teeth are encapsulated in a nonmagnetic structure, allowing a more compact design.